Community Structure of coral ecosystems in sites of importance for the conservation of marine biodiversity in the North Pacific of Costa Rica. - Mena, Sebastián; Quesada-Perez, Fabio; Sánchez-Noguera, Celeste; Salas-Moya, Carolina; Alvarado, Juan José; López-Garro, Andrés; Zanella, Ilena; Méndez Venegas, Mauricio; Piedra-Chacón, Rotney; Anderson Rana, Lara; Fonseca López, Luis (Revista de Biología Tropical, 2025)
Introduction: The North Pacific of Costa Rica is a very dynamic region in oceanographic terms and has been identified as an important site for coral environments, with abundant coral communities and some of the most developed coral reefs on the Costa Rican Pacific coast. Nevertheless, these ecosystems have suffered degradation in the last years, a product of events of natural and anthropogenic origin. Objective: This study determines the ecological state of the coralline ecosystems located in the Sites of Interest for the Conservation Golfo de Papagayo and Punta Gorda - Punta Pargos. Methods: The coastline and geological formations (islands and islets) located in these SICs were explored, and rapid ecological evaluations were carried out, which included the characterization of the benthic, macroinvertebrate, and fish communities of each site. Results: In 46 surveyed sites, three were identified as living coral reefs, 14 as dead coral reefs, and 29 as coral communities upon basalts, highlighting a low coverage of live coral (4.3 %) and a predominance of algae mats (64 %). A total of 79 fish species and 40 macroinvertebrate species were recorded, with significant variations in the community composition of these organisms between the three types of coral ecosystems characterized. Matapalo and Jícaro stand out as bright spots of reef development in the region. Conclusions: This evaluation sheds light on the continuous alteration of these ecosystems over the last decades, without signs of significant improvements in their state. This reality underlines the urgency of taking effective measures of conservation and management to preserve and restore these coral and rocky reefs, in order to guarantee the sustainability of these valuable marine resources in the region.